Implementation of Ministerial Regulations Based on Attribution Power in the Administration of Government - M. Yasin al Arif (Jurnal Mulawarman Law Review, 2023)
This research aims to analyze the incompatibility of Ministerial regulations in the implementation of government which are formed based on attribution of power and intends to formulate a concept to prevent Ministerial regulations from resulting in regulatory obesity. The focus of this research is to answer the questions regarding the position of Ministerial regulations within the Indonesian legal system and how the incompatibility of Ministerial regulations based on attribution power affects the administration of government. This paper is a normative research using secondary data and literature study for data collection.The research findings indicate that firstly, within the legislative regulations system, Ministerial regulations are considered as delegated legislation or delegated regulations based on regulations above them. Secondly, through the independent authority of ministries and/or Ministers, a wide scope has been opened for creating regulations based on the independent authority of Ministers and/or ministries. This has resulted in an anomaly, namely the emergence of laws that provide attribution power to Ministers and/or ministries to directly create Ministerial regulations. This situation creates incompatibility in the administration of government because attribution power cannot be exercised by Ministers as assistants and mandate holders of the President.